Avaliação da segurança do extrato hidroetanólico da entrecasca do caule de Virola elongata (Benth.) Warb em modelos experimentais in vitro e in vivo - Carvalho, Michellen Santos de (2024)
Virola elongata (Benth.) Warb. (Myrsticaceae), popularly known as "mucuíba", is a native tree species that can be found in the Amazon Rainforest regions of South America and the Tropical Forests of Central America. The macerated extracts from the stem bark of this tree have traditionally been used to treat various health problems, including gastric ulcers, infections, and inflammation. V. elongata has demonstrated pharmacological properties such as antiulcer, gastroprotective, antiproliferative, antimitotic, as well as psychoactive effects. The objective of the present study was to evaluate the toxicity of the hydroethanolic extract from the stem bark of Virola elongata (HEVe) in in vivo and in vitro experimental models. HEVe was obtained by macerating stem bark powder in 70% hydroethanolic solution (1:10 w/v). The cytotoxicity of HEVe (3.125-200 µg/mL) was evaluated by Alamar blue assay in Chinese hamster ovary epithelial cells (CHO-k1) and human gastric adenocarcinoma (AGS). The evaluation of the genotoxicity of HEVe (10, 30 or 100 µg/mL) was carried out in CHOk1 cells using the micronucleus test. The acute toxicity of HEVe was evaluated by oral administration of a single dose (2,000 mg/kg) in mice of both sexes. The subchronic toxicity of HEVe was evaluated by oral administration, for 30 days, in rats, of 300, 600 or 1,200 mg/kg of the extract. Clinical observations of toxicological parameters were noted and grouped every 6 days. After the treatment period, blood was collected for hematological and biochemical analysis, and some organs were removed for macroscopic and histopathological analysis. HEVe did not show cytotoxicity in CHO-K1 and AGS cells (IC50 > 200 μg/mL) and did not cause DNA damage in CHO-k1 cells. Oral administration of HEVe in a single dose of 2,000 mg/kg did not result in the death of mice, with a reduction in body weight variation (33.03%, p < 0.05) and an increase in the relative weight of the stomach (12.82%, p < 0.05) in male mice, and increased relative spleen weight (25.00%, p < 0.01) in female mice. In the evaluation of subchronic toxicity, HEVe did not result in the death of the animals over the 30 days. A reduction (p < 0.05) in water consumption of 36.65% and 34.12% was observed in the groups treated with 300 and 600 mg/kg of HEVe, respectively, on D6, and urinary excretion of the treated animals with 600 mg/kg of HEVe showed an increase (p < 0.05) throughout the experiment, with a maximum value of 46.72% on D12. Blood counts showed that the dose of 300 mg/kg reduced (p < 0.05) the absolute number of lymphocytes, while doses of 300, 600 or 1200 mg/kg of HEVe reduced the red blood cell count in whole blood. in 24.84% (p < 0.01), 16.72% (p < 0.05) and 22.14% (p < 0.01), and the absolute number of monocytes (p < 0.05) at 59.77%, 65.51%, and 79.81%, respectively. As for biochemical parameters, the glucose level was found to increase by 22.41% (p < 0.05) only at the highest dose, while creatinine was reduced by 44.71% (p < 0.05) at the 300 mg/ kg of HEVe. In animals with the three doses tested, plasma levels of AST and alkaline phosphatase showed a reduction (p < 0.05) with the vehicle group. However, the hematological and biochemical changes observed are within physiological limits for this animal species. No macroscopic and histopathological changes were observed in the organs of animals treated with the three doses of HEVe over a period of 30 days. The results showed that HEVe did not present cytotoxicity or genotoxicity in vitro. HEVe has proven safe in rodents in acute and subacute toxicity tests. In rats, the no observed adverse effect level (NOAEL) dose was greater than 1200 mg/kg orally.